DESIGN OF DRAINAGE SYSTEM BASED ON ECODRAINAGE IN BUMI PANYAWANGAN HOUSING, CILEUNYI DISTRICT, BANDUNG REGENCY, WEST JAVA - Nugraha Ramdhani, Indra
The rapid development of infrastructure in the Bandung area has led to changes in land use. This makes it more difficult for rainwater to seep into the ground, so the amount of runoff water on the surface will be greater which increases the risk of flooding in downstream areas. The Bumi Panyawangan housing estate has an area of 45 ha with a land elevation of around 685-662 mdpl, in the administrative area of Cileunyi District. The soil type in the Bumi Panyawangan Housing according to USCS is silt clay (CH) with HSG D group. With the problem of flooding at several points of the channel, it is necessary to evaluate and redesign the existing drainage as well as add ecodrainage technology to the drainage system of the Bumi Panyawangan Housing. The redesign and design of ecodrainage technology was made with the help of the EPA SWMM 5.1.5 application. In the analysis of rainfall intensity, the average rainfall values at PUH 10 & PUH 25 were 124.99 mm/hour and 142.87 mm/hour using the Van Breen – Talbot method. The Bumi Panyawangan housing estate is located in the Cikeruh sub-watershed within the Citraum watershed area which has water inlets coming from 2 Cikeruh tributaries and 1 from residential catchment areas. The Bumi Panyawangan housing estate has 3 catchment areas, namely water catchment area Sub-DAS 1 of 23 catchment area, water catchment area Sub-DAS 2 of 8 catchment area, and water catchment area Cluster of 17 housing clusters. The main drainage in Bumi Panyawangan Housing has a natural pattern with an average of square and trapezoidal drainage shape. Bumi Panyawangan housing has 75% imperviousness, with C PUH 10 and PUH 25 being 0.68 & 0.74, respectively. The results of SWMM modeling with dynamic wave flow routing show that the total runoff inflow at the 25-year PUH is around 10.763 m3 /s and the discharge discharge is 9.739 m3 /s. As for the existing canal, several flood points have occurred with a PUH of 25 years. From the modeling results show that there are channels that exceed the speed criteria limit. These channels need to be dimensionally changed in order to reduce the speed of water flow and flooding at the surrounding nodes so that they fit the criteria. The ecodrainage technology that will be applied is based on the concept of the Sustainable Urban Drainage System (SUDS). The technology chosen is ecodrainage which focuses on water quantity and water conservation. After analyzing based on soil characteristics, topography, flow routes, and existing land, the selected ecodrainage technology is pond & wetland with type of wetpond and ecodrainage at the source is RWH (Rain Water Harvesting). The location chosen for wetpond is location 2 with offline wetpond type and the location for RWH is in the yard of the house. Based on the calculations, the dimensions of the offline wetpond have a base area of 702 m2 , a surface area of 1980 m2 and a depth of 3 m with a cut pyramid shape. While the dimensions for the RWH are 1.3 m x 1.3 m with a height of 1.2 m, RWH type is PAH Masonry with 2 m3 typical PAH type